Penerapan Origami Tenun Lurik Pada Ready To Wear Deluxe Bergaya Futuristik - Najmadini, Arini; Fitra, Annisa; Handayani, Wuri (Style : Journal of Fashion Design, 2024)
The creation of ready-to-wear deluxe is based on the creator's desire to develop clothing made from lurik weaving with origami techniques on ready-to-wear deluxe with futuristic styles. This is because rarely to find ready-to-wear deluxe made from lurik materials with origami techniques in futuristic styles. In connection with this, the purpose of creating this work is to give a new form of ready-to-wear deluxe futuristic style made from lurik weaving with origami techniques which is expected to be one of the references for the development of lurik weaving. The creation method uses a three-stage design process approach consisting of definition & research, creative exploration, and implementation. The result of this creation process is six looks of ready-to-wear deluxe that will be presented at Jogja Fashion Parade 2024.